Sinonasal Phosphaturic Mesenchymal Tumor: A Rare and Misinterpreted Entity - Arnaoutakis, Demetri; Naseri, Iman (Journal of Neurological Surgery Reports, 2015)
Objectives Oncogenic osteomalacia is a paraneoplastic syndrome in which the tumor secretes a peptide-like hormone, fibroblast growth factor, resulting in urinary loss of phosphates.Methods We present the case of a 50-year-old woman with a benign phosphaturic mesenchymal tumor (PMT) involving the ethmoid sinus with obstruction of the ostiomeatal complex causing unilateral nasal airway obstruction.Results The tumor was initially thought to be an esthesioneuroblastoma based on primary pathology interpretation and on clinical and radiographic appearance. However, a benign PMT was later confirmed by further testing.Conclusion The tumor was removed entirely by the endoscopic transnasal approach, leading to a full resolution of symptoms.
Keywords: phosphaturic mesenchymal tumor; skull base resection; endoscopic sinus surgery